Impact Of Solar Photovoltaic System On Transformer Tap Changer In Low Voltage Distribution Networks - Gan, Chin Kim; Lau, Cheiw Yun; Sulaima, Mohamad Fani; Salam, Zainal (Elsevier, 2016)
This paper investigates the impact of solar resource variability on the operation of a low-voltage On-Load-Tap-Changer (OLTC) in a generic distribution network from the Malaysian grid. The OLTC's operation is studiedin two different weather conditions—sunny and cloudy days. The aspects analysed are the OLTC's time delay setting, PV penetration levels and PV installation location. The results suggest that the number of tap changes in a cloudy day is approximately 1.5 times higher than in a sunny day. In addition, at 50% PV penetration level on a cloudy day, the OLTC operation increases by 38% and it is doubled at 100% penetration.